Hot and Cool Executive Function in Elite- and Amateur- Adolescent Athletes From Open and Closed Skills Sports - Holfelder, Benjamin; Klotzbier, Thomas Jürgen; Eisele, Moritz; Schott, Nadja (Frontiers in Psychology, 2020)
Executive functions (EF) not only play an important role in shaping adolescent’s goal-directed, future-oriented cognitive skills under relatively abstract, non-affective conditions (Cool EF), but also under motivationally significant, affective conditions (Hot EF). Empirical evidence suggest a link between EF, exercise and physical activity, specifically elite athletes appear to outperform amateur athletes in Cool EF; however, no studies have examined the relationship between Hot and Cool EFs and impulsivity during the developmentally sensitive period of adolescence comparing different types of sport (open- vs. closed-skills), and levels (elite athletes vs. amateurs). A total 86 boys and girls between 13 and 15 years of age (M=14.0, SD=0.79) from different sports (track-and-field; team handball) were recruited. Participants were further divided into two groups: a) 40 elite, and b) 46 amateur athletes. They completed four Cool EF tasks including Trail-Making Test, Trail-Walking-Test, Flanker-task, n-back-task, and one Hot EF task on Game of Dice-task. Data on subjective impulsivity (UPPS Impulsive Behavior Scale; Barratt Impulsiveness Scale-15) was also collected. There was a significant overall effect for expertise in favor of elite athletes (Wilks’ Lambda=0.61, F(14,69) = 3.19, p=.001, ɳ2p=.393), but no overall main effect for type of sport or an interaction for expertise by type of sport. Specifically, elite athletes showed significantly better performances on dual tasks. For Hot EF, there were no main effects for type of sport, expertise level, training experience or training duration. We also found positive correlations among Cool EF and impulsivity measures, and between Hot EF and Impulsivity, but no significant relationship between Cool and Hot EF. The current understanding of the decisive cognitive abilities does not correspond to sporting reality, so that the tests frequently used are not sensitive enough to distinguish between elite and amateur athletes or different sports. However, it should also be remembered that the factors underlying complex sporting performance are multidimensional and are obviously difficult to trace back to selected partial aspects. Without being able to answer this conclusively, we proposed a 4-D classification of experimental paradigms, in which we differentiate between tasks of different specificity, Cool and Hot EF, and task complexity, and type of sport.